Analysis Of The Construction Time Of The Cilutung Sumedang Bridge – Majalengka - Aditya Nurfikri Julistitian; Melvin Solehudin; Muhammad Asif; Aryati Indah Kusuma (Journal of World Science, 2025)
Project management is the process of managing limited resources in an efficient, effective, and timely way to complete a project according to a predetermined plan. The three main functions in project management include the planning, execution, and control processes. This control includes the management of various project resources such as manpower, equipment, materials, and methods used. In order to achieve optimal project performance results in the construction work of the Cilutung Bridge, various analyses were carried out aimed at supporting the smooth implementation of the project in accordance with the plan. In this study, the analysis applied is to calculate the volume of work, implementation planning, and estimate the needs of labor, materials, and equipment, accompanied by the preparation of an s-curve and the analysis of the critical path CPM (Critical Path Method) as an analysis step to assess the performance of the project to ensure its implementation is on schedule and achieve optimal conditions. The results of the study show that from the results of the calculation of the volume of work in the Cilutung Sumedang – Majalengka Bridge Construction Project is 12257.813 m3. Then using CPM (Critical Path Method) analysis takes 72 days or equal to 18 weeks.